Preparation of heterogeneous catalyst for the transesterification of waste cotton seed oil - Kaur, Satwinder (My University, 2013)
A series of WO3/SiO2–600 catalysts has been prepared by impregnating 5–25 wt% sodium tungstate dihydrate in silica by wet chemical method. Prepared WO3/SiO2–600 catalysts has been characterized by powder X–ray diffraction, scanning electron microscopy, BET surface area, and Hammett indicator test studies in order to correlate the catalyst structure and acidic strength with its activity. The prepared 20–WO3/SiO2–600 has been employed as heterogeneous catalyst for the transesterification of waste cotton seed oil (containing 4.9 wt% free fatty acid contents) with methanol. Under optimal reaction conditions viz., methanol/oil molar ratio of 80:1, catalyst to oil weight fraction of 5 % and 65 °C reaction temperature, a 98±2 % fatty acid methyl ester (FAME) yield was obtained in 5 h of reaction duration. Under the same reaction conditions, the activation energy was found to be 37.71 kJ mol-1. Few physicochemical properties of the prepared biodiesel sample from waste cottonseed oil have been studied and compared with EN standard values.
Master of Science-Chemistry, Dissertation
Keywords: sodium tungstate dehydrate; WO3/SiO2- 600 catalyst